2014
DOI: 10.5603/fhc.2014.0008
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Graves’ disease with methimazole in children alters the proliferation of Treg cells and CD3+ T lymphocytes

Abstract: Almost all cases of hyperthyroidism in children result from Graves' disease (GD). Recent studies have confirmed a significant role of T regulatory cells (Tregs) in the development of autoimmune diseases. However, the interactions between T cell responses and Treg proliferation in GD are still poorly understood. The aim of this study was to assess the proliferation of Treg cells (Tregs) and CD3+ T lymphocytes isolated from 50 children with GD before and after treatment with the thyreostatic drug methimazole (MM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 31 publications
1
8
0
1
Order By: Relevance
“…It has recently been demonstrated that ATD could normalize circulating Treg frequency in G patients [10,11,25]. Our results extend these data and demonstrated that an ATD pretreatment moderate the immune changes induced by RAI therapy: less variation of Treg frequency, a trend to less defective Treg function and restoration of normal levels of suppressive cytokines.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…It has recently been demonstrated that ATD could normalize circulating Treg frequency in G patients [10,11,25]. Our results extend these data and demonstrated that an ATD pretreatment moderate the immune changes induced by RAI therapy: less variation of Treg frequency, a trend to less defective Treg function and restoration of normal levels of suppressive cytokines.…”
Section: Discussionsupporting
confidence: 86%
“…For example, in GD patients taking methimazole, a decrease in TSHR-Ab levels [24] and an increase in peripheral activated Treg [11,25] were described.…”
Section: Introductionmentioning
confidence: 99%
“…Klatka et al also demonstrated that co-cultures of CD3 + T cells and Tregs showed that Tregs were not capable of efficiently inhibiting the proliferation of CD3 + T cells in GD patients. In conclusion, the authors suggest that Treg cells are partly dysfunctional in GD disease and are probably suppressed by CD3 + T cells and that methimazole exerts some immunomodulatory effect [22].…”
Section: Discussionmentioning
confidence: 92%
“…Recently, decreased frequencies of Tregs in PBMCs of the GD patients [20][21][22] and GO patients [23] compared vs. the normal subjects were demonstrated. Bossowski et al found in untreated children with GD and Hashimoto thyroiditis (HT) the significant decrease in CD4 + Foxp3 and CD4 + CD25 high T lymphocytes compared to the healthy controls [20].…”
Section: Discussionmentioning
confidence: 99%
“…Tregs account for approximately 5–10% of peripheral blood (PB) CD4 T cells. Tregs include two subtypes: Natural Tregs (nTregs; primarily refers to Tregs formed in the embryo/newborn thymus, also described as thymus Tregs or tTregs); and inducible Tregs (iTregs; predominantly induced in vitro , also termed PB Tregs or pTregs) ( 3 ). Recent studies indicated that CD4 + CD25 + Tregs were significant in various types of autoimmune disease ( 4 , 5 ), and CD4 + CD25 + Treg abnormalities may contribute to the occurrence and progression of hyperthyroidism ( 6 ).…”
Section: Introductionmentioning
confidence: 99%